Corporate Size Relations, Audit Opinion, Reputation of Public Accounting Offices, Institutional Ownership of Timeliness for Delivery of Financial Statements the Manufacturing Company Listed in Indonesia Stock Exchange - Darmiathi, Darmiathi; Anzib, Nuraini (Universitas Syiah Kuala, 2019)
Objective This study aims to examine the relationship of company size, audit opinion, the reputation of public accounting firms, and institutional ownership on the timeliness of financial statement submission. The four independent variables will be tested with the dependent variable, namely the timeliness of financial statement submission.Design/methodology The sample of this research is 327 companies that have financial statements on the Indonesia Stock Exchange during the 2015-2017 observation year. The analytical method used in this study is correlational analysis.Results The results of this study indicate that the size of the company, the reputation of the public accounting firm, and institutional ownership are related to the timeliness of financial statement submission, while the audit opinion shows no relationship with the timeliness of financial statement submission. Keywords: Timeliness of Financial